Potential Responses to the COVID-19 Outbreak in Support of Migrant Workers - Moroz, Harry; Shrestha, Maheshwor; Testaverde, Mauro (World Bank, Washington, DC, 2020)
The note describes the key challenges facing the health, livelihoods, and mobility of internal and international migrants and their families due to the COVID-19 (Coronavirus) outbreak. The note presents the policy options available to governments to address these challenges and describes the assistance that the World Bank can offer in areas related to social protection and jobs to support these efforts. The living and working conditions of internal and international migrants make them vulnerable to contracting COVID-19 (Coronavirus). Measures put in place to control disease transmission both within and across countries have resulted in significant disruption in transportation networks and in labor markets that have hit migrant workers hard. The resulting decline in remittances will transmit these negative impacts to the families of migrants. Travel restrictions may lead to labor shortages in critical sectors like agriculture that are dominated by migrant workers. While the specific type of support that should be targeted to migrants depends on location, legal status, and type of migration, most migrants will need access to safety nets in the form of cash or in-kind assistance to support them as they comply with transmission control measures and cope with the impacts of the crisis. Policies to support employment retention and promotion will be particularly important as a complement to these safety nets for internal migrants and migrants returning from abroad. Policies to offset the expected declines in remittances will be important for all migrants and their families. Programs created to respond to the COVID-19 (Coronavirus) outbreak should be migrant-sensitive to take into account the unique challenges facing migrants.